Are there opportunities to improve care as patients transition through the cancer care continuum? A scoping review - Diane Lorenzetti; Shamir Chandarana; Areej Hezam; Abigail Thomas; Seremi Ibadin; Jaling Kersen; Stefan Kurbatfinski; Joseph C Dort; Khara M Sauro (BMJ Open)
Purpose Patients with cancer experience many Transitions in Care (TiC), occurring when a patient’s care transfers between healthcare providers or institutions/settings. Among other patient populations, TiC are associated with medical errors, patient dissatisfaction and elevated healthcare use and expenditure. However, our understanding of TiC among patients with cancer is lacking.Objective To map and characterise evidence about TiC among patients with cancer.Participants Adult patients with cancer at any stage in the cancer continuum.Intervention Evidence sources exploring TiC among patients with cancer were eligible.Outcome Evidence sources exploring TiC among patients with cancer using any outcome were eligible.Setting Any setting where a patient with cancer received care.Design This scoping review included any study describing TiC among patients with cancer with no restrictions on study design, publication type, publication date or language. Evidence sources, identified by searching six databases using search terms for the population and TiC, were included if they described TiC. Two independent reviewers screened titles/abstracts and full texts for eligibility and completed data abstraction. Quantitative data were summarised using descriptive statistics and qualitative data were synthesised using thematic analysis.Results This scoping review identified 801 evidence sources examining TiC among patients with cancer. Most evidence sources focused on the TiC between diagnosis and treatment and breast or colorectal cancer. Six themes emerged from the qualitative evidence sources: the transfer of information, emotional impacts of TiC, continuity of care, patient-related factors, healthcare provider-related factors and healthcare system-related factors. Interventions intended to improve TiC among patients with cancer were developed, implemented or reviewed in 163 evidence sources.Conclusion While there is a large body of research related to TiC among patients with cancer, there remains a gap in our understanding of several TiC and certain types of cancer, suggesting the need for additional evidence exploring these areas.